Residual aluminium in water intended for human consumption - Krupińska, Izabela; Płuciennik-Koropczuk, Ewelina; Gągała, Sylwia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Aluminium is one of the environmental factors that may have an impact on Alzheimer`s and Parkinson`s disease. Some epidemiological studies show a relationship between the concentration of aluminium in drinking water and the incidence of Alzheimer`s disease. The article presents and discusses the results of research on the effect of the type and dose of non-prehydrolyzed aluminium coagulants on the concentration of residual aluminium in water intended for human consumption.
Keywords: potable water; residual aluminium; coagulation; non-prehydrolysed coagulant; environmental factors; epidemiological studies; woda pitna; resztki aluminium; koagulacja; koagulanty niehydrolizowane; czynniki środowiskowe; badania epidemiologiczne